Integrating synthetic biology and laboratory-on-a-chip technologies for next-generation biosensors - David, Gabrielle; Cai, Yizhi (Frontiers in Lab on a Chip Technologies, 2026)
Biosensors harness biological components to detect and report on specific analytes, offering crucial insights across medicine, environmental monitoring, agriculture, and food security. The convergence of synthetic biology and laboratory-on-a-chip (LoC) technologies is enabling a new generation of biosensors that are programmable, modular, and field-deployable. Synthetic biology provides engineered sensing elements, including bespoke proteins, aptamers, and genetic circuits, that expand the range of detectable analytes while offering tunable sensitivity, specificity, and dynamic range. LoC platforms, in turn, miniaturize fluid handling and analytical processes into integrated microfluidic devices, creating controlled environments that enhance biosensor performance, portability, and biocontainment. Together, these approaches address long-standing barriers in biosensing by coupling biological programmability with physical precision. This review surveys the applications of synthetic biology-LoC integration, from healthcare and environmental monitoring to emerging frontiers, including biocomputing and deep sea exploration. With rapidly accelerating innovation, the potential of these devices can be realized, reshaping the way we diagnose disease, safeguard ecosystems, manage food supplies, and explore new frontiers.